(untitled) (Revista de Investigaciones Universidad del Quindío, 2021)
This article describes and explains what happens after holding a procedure, which results in a reparatory agreement (AR), using alternative dispute resolution mechanisms (MASC), provided for in the National Law of Alternative Mechanisms for the Resolution of Controversies in Criminal Matters (LNMASCMP), depending on the appropriate case; conciliation, mediation and the restorative meeting, which are held between the victim or offended and the accused. Once said AR has been held, there is an area that is in charge of monitoring, which has to comply with certain functionality. The 2008 reform to the Political Constitution of the United Mexican States (CPEUM) in its article 17, fourth paragraph, creates the LNMASCMP which, as of its publication in 2014, governs alternative mechanisms in criminal matters. However, there is a lack of knowledge about the handling or management after holding an RA, in particular of the PR monitoring area of ​​the Attorney General’s Office of the State of Tabasco (FGE), as well as the role it plays when having knowledge of the subscription deferred AR, which are stipulated in numeral 36 of the (LNMASC) in its different sections.